Júpiter, emperador romano. La lectura política de la Tebaida de Estacio (Minerva, 2019)
The American critical sector, facing off against the European school, assures us that in his Tebaid Statius offers a pessimistic and negative view of the reign of the Flavians, being William J. Dominik the leading supporter of this kind of political reading. In agreement with the antropological theory that the poet may reflect a socio-political reality using the myth, the Anglo-american critical sector affirm that Statius delivers a clear message under the fictional guise of myth for those willing to listen and that Vespasian and his children find parallels not only among the human characters of the Tebaid, but also in the divine figures. Despite the fact that there are weighty arguments against the existence in the Thebaid of an anti-Domitian political reading, I do not belive that we habe sufficient data to be able to completely deny Dominik’s conviction that Statius mythically reflects a disastrous present. In the present paper I have tried to support his thesis, since the study of Statian theology bases it.